Analisis Kemampuan Keuangan Daerah Kota Makassar - Muh Nur R (BALANCE: Economic, Business, Management and Accounting Journal, 2019)
ABSTRACT  This study aims to answer a number of key issues, including: (1) What is the level of financial capacity in the city of Makassar, (2) What is the contribution of local revenue to the regional income and expenditure budget in the city of Makassar. Regional financial capacity in the era of regional autonomy is often measured using PAD performance. The method used in this study is descriptive quantitative and the types of relevant research such as triangles on regional financial data. The analysis technique used is the Routine Financial Ability Index (IKR) determined by BAPPENAS. While the data used is the APBD of the city of Makassar in 2011-2015. The results of the study show that regional financial independence ratios have an average yield of 50.60% or are in a pattern of participatory relationships. The ratio of the degree of fiscal decentralization and the ratio of routine ability index that shows the ability of regional finances is quite good, amounting to 30.92% and 37.42%. In the harmony ratio, routine expenditure is greater than development spending. The contribution of PAD to the APBD was 31.03%. By looking at the results of the analysis, the development of the financial capacity of Makassar City in 2011-2015 was considered quite good.Keywords                   : Ratio, Finance, Performance, IndependenceCorrespondence to       : muhnur@unismuh.ac.id ABSTRAK  Penelitian ini bertujuan untuk menjawab beberapa permasalahan pokok, antara lain: (1) Bagaimana tingkat kemampuan keuangan daerah kota Makassar, (2) Bagaimana kontribusi pendapatan asli daerah terhadap anggaran pendapatan dan belanja daerah di kota Makassar. Kemampuan keuangan daerah dalam era otonomi daerah sering diukur dengan menggunakan kinerja PAD. Metode  yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dan jenis-jenis penelitian yang relevan seperti triangulasiterhadap data-data keuangan daerah. Teknik analisis yang digunakan adalah Indeks Kemampuan Keuangan Rutin (IKR) yang ditetapkan oleh BAPPENAS. Sedangkan data yang digunakan digunakan adalah APBD kota Makassar tahun 2011-2015. Hasil penelitian menunjukkan rasio kemandirian keuangan daerah yang memperoleh hasil rata-rata sebesar 50,60% atau berada pada pola hubungan partisipatif. Rasio derajat desentralisasi fiskal dan rasio indeks kemampuan rutin yang menunjukkan kemampuan keuangan daerah cukup baik, yaitu sebesar 30,92% dan 37,42%. Pada rasio keserasian, pengeluaran belanja rutin lebih besar dibandingkan dengan belanja pembangunan. Konstribusi PAD terhadap APBD sebesar 31,03%. Dengan melihat hasil analisis tersebut, perkembangan kemampuan keuangan Kota Makassar tahun 2011-2015  dianggap cukup baik.Kata kunci                  : Rasio, Keuangan, Kinerja, KemandirianKorespondensi             : muhnur@unismuh.ac.id